Neopterin: A Promising Candidate Biomarker for Severe COVID-19 - Hailemichael W (Dove Medical Press, 2021)
Wasihun Hailemichael,1 Mulugeta Kiros,2 Yibeltal Akelew,3 Sisay Getu,4 Henok Andualem1 1Immunology and Molecular Biology, Medical Laboratory Science, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2Medical Microbiology, Medical Laboratory Science, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 3Immunology and Molecular Biology, Medical Laboratory Sciences, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 4Hematology and Immuno-Hematology, Medical Laboratory Science, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Wasihun HailemichaelImmunology and Molecular Biology, Medical Laboratory Science, College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaTel +251 946111414Email wasihunh383@gmail.comAbstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection has rapidly spread across the world since its first emergence in China in late 2019. It is a major public health concern with no effective treatct 3ments. The immunopathology of SARS-CoV-2 is associated with an excessive inflammatory response. Macrophage activation syndrome (MAS) is also associated with the severity of the disease in SARS-CoV-2-infected patients. Neopterin is a macrophage activation marker produced by monocytes and macrophages upon activation by interferon-gamma (IFN-γ). Neopterin is a well-established marker in a variety of diseases, and recent evidence indicates that it could be helpful in early prediction of the severity of COVID-19 disease and serve as a prognostic marker. Here, we outline the role of macrophage activation syndrome in the pathogenesis of SARS-CoV-2 and suggest that neopterin could be used as a biomarker for progression of COVID-19.Keywords: neopterin, biomarker, MAS, SARS-CoV-2, COVID-19